Analisis kluster Kabupaten dan Kota di Provinsi Jambi berdasarkan indikator pembangunan - Rahmadi, Selamet (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study is to classify Regencies and Cities in Jambi Province based on HDI, economic growth, percentage of population growth, percentage of poor population, percentage of open unemployment rate and Gini ratio. To answer these objectives the hierarchical method used is Average Linkage (Between Groups). The of analysis were obtained, two clusters could be formed, where group 1 consisted of 10 Regencies and Cities, group 2 consisted of 1 Regencies. Â